Exploring women’s dietary diversity amidst climate variability: A comparative analysis across eight low- and middle- income countries - Carducci, B.; Benedict, R.; Corrigan, J.; Mayala, B.; Namaste, S.; Bilotto, F.; Cao, P.; Herrero, M.; Guo, Zhe; Fanzo, J. (IOP Publishing, 2025)
It is anticipated that climate change and climate variability will threaten food and nutrition security through multiple pathways, yet evidence on its impact on minimum dietary diversity for women (MDD-W),especially in low- and middle- income countries (LMICs) is limited. Using Bayesian hierarchical statistical modeling, we analyzed the impacts of climate variability on MDD-W, of 142 484 non-pregnant women, aged 15–49 years, in eight LMICs (Burkina Faso, Cambodia, Cˆote d’Ivoire, Ghana, Kenya, Mozambique, Nepal and Tanzania). All analyses were adjusted for survey weights and sampling design and analyzed separately. The proportion of women achieving MDD-Wtheprevious day of the survey ranged between 20.8% and 57.3%. In the full model, enabling variables including climate change and variability generally showed significant negative associations with MDD-W (precipitation and land surface temperature anomalies, daytime and nighttime long-term land surface temperature variability), whereby the adjusted odds of women’s dietary diversity was reduced by 9%–37% due to climatic variables. Underlying variables such as growing season, nutrient yield and enhanced vegetation index had limited associations across countries. In fact, for nutrient yields, the direction of association differed by country and nutrients. Immediate variables were significantly positively associated with MDD-W in almost all countries with an adjusted odds of women’s dietary diversity increasing by 6%–92%, including household wealth (n = 8), women’s media access (n = 8), women’s education (n = 7), improved sanitation and women’s employment (n = 5) and women’s landownership (n = 3). The month of the survey was associated with MDD-W in four countries, but the direction of association varied by country. These findings suggest that safeguarding women’s diet diversity from climate change requires adaptation efforts that target vulnerable populations to ensure nutrition.